Method for Producing Flower-Like Zn-P-O Zinc Phosphate Particles and Particles Produced Therefrom

By controlling the molar ratio and reaction conditions, the method achieves reproducible flower-shaped Zn-PO-based zinc phosphate particles with enhanced stability and UV protection, addressing shape and performance inconsistencies in existing manufacturing methods.

KR103041114B1Active Publication Date: 2026-10-30BM PORT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250184053
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2025-11-07
Filing Date
2025-11-27
Publication Date
2026-10-30
Estimated Expiration
2045-11-27

AI Technical Summary

Technical Problem

Existing methods for manufacturing zinc phosphate particles lack precision in controlling particle shape, size, and surface characteristics, leading to inconsistent performance and stability in applications due to variations in synthesis and post-processing conditions.

Method used

A method for producing flower-shaped Zn-PO-based zinc phosphate particles by controlling the molar ratio of zinc to phosphorus, reaction conditions, and pH levels during the mixing and stirring process, ensuring consistent flower-shaped formation.

Benefits of technology

The method produces reproducible flower-shaped particles with controlled crystallinity and surface characteristics, enhancing dispersion stability and UV protection properties, suitable for cosmetic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112025133790509-PAT00009_ABST
    Figure 112025133790509-PAT00009_ABST
Patent Text Reader

Abstract

A manufacturing method provided as one embodiment of the present invention relates to a method for manufacturing flower-shaped Zn-PO-based zinc phosphate particles having a unique shape, and is based on establishing an optimal manufacturing protocol to obtain specific physical properties and shapes compared to conventionally known zinc phosphate particles by specifically setting the molar ratio between reactants and reaction conditions. Since the particles manufactured therefrom exhibit differentiated technical effects compared to conventional technology based on their uniqueness, their practical value is expected to be high.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing flower-shaped Zn-PO-based zinc phosphate particles and particles manufactured therefrom. Background Technology

[0003] Zn-PO zinc phosphates are a group of inorganic compounds composed of zinc (Zn), phosphorus (P), and oxygen (O), and are known to exhibit various crystal phases, surface structures, and morphologies depending on synthesis conditions. Generally, the crystallinity, particle size, surface roughness, and shape of zinc phosphates vary significantly depending on changes in the type of precursor, reaction temperature, reaction solvent, pH, ion concentration, and reaction time. These particle characteristics are factors that determine performance in various application environments, such as dispersion stability, interfacial interactions, and physical properties within formulations.

[0004] The synthesis process of inorganic particles is generally divided into an initial nucleation stage and a subsequent crystal growth stage, and variables such as the nucleation rate, relative concentration of ions, and dissolution-repreneurship equilibrium conditions directly affect the average size and particle size distribution of the particles. Zinc phosphate-based particles also exhibit changes in crystallinity, particle structure, and aggregated structure depending on minute variations in the reaction environment, and these differences can cause significant changes in the final physical properties even among particles with the same composition.

[0005] Post-synthesis processing (e.g., washing, drying, dispersion, surface modification) also plays a significant role in particle characteristics. In particular, particle dispersibility is a key factor independent of the composition itself; if particle aggregation occurs, it is difficult to ensure homogeneity of the final formulation, and it can negatively affect appearance quality and usability. On the other hand, if the surface condition is uniform and the dispersion process is properly controlled, stable dispersion within the medium and long-term stability can be ensured.

[0006] As such, even if zinc phosphate particles have the same elemental composition, their phase structure, crystallinity, particle size distribution, and surface characteristics can vary significantly depending on synthesis and post-processing conditions; these variations are directly linked to the reproducibility and quality stability of application products. Therefore, to manufacture zinc phosphate particles or utilize them as functional materials, a technical approach capable of precisely controlling reaction conditions throughout the particle generation, growth, and post-processing stages is essential. Prior art literature

[0008] Korean Registered Patent No. 2789869 The problem to be solved

[0009] The main purpose of the present invention is to provide a method for manufacturing flower-shaped Zn-PO-based zinc phosphate particles and particles manufactured therefrom.

[0010] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0012] As one embodiment of the present invention, a method for producing flower-shaped Zn-PO-based zinc phosphate particles is provided, comprising the steps of: mixing a zinc source solution and a phosphorus source solution; and stirring the mixed solution.

[0013] The above-mentioned Zn-PO-based zinc phosphate particles are inorganic compounds containing zinc (Zn), phosphorus (P), and oxygen (O), and are zinc phosphate-based particles having a Zn-PO ternary composition. The particles may be in the form of a single crystalline phase or a mixture of multiple Zn-PO-based phases, which can be controlled according to manufacturing conditions. The particles may include zinc phosphate phases such as ZnHPO4, Zn3(PO4)2, Zn2P2O7, or a mixture thereof, and may have a composite structure in which ZnO or Zn(OH)2 components remain, if necessary.

[0014] In the above method, the term "flower shape" may refer to a shape in which a plurality of petal shapes are aggregated toward the center, and the plurality of petal shapes may be two or more, three or more, four or more, five or more, six or more, seven or more, eight or more, nine or more, or ten or more, but are not limited thereto. The plurality of petals may have various characteristics such as surface size, outer perimeter length, anisotropy, sphericity, convexity, and rigidity, and the plurality of petals may be a shape in which they are aggregated symmetrically with respect to the center.

[0015] In the above method, the step of mixing the zinc source solution and the phosphorus source solution may be a step of mixing the zinc source solution and the phosphorus source solution such that the molar ratio of zinc to phosphorus is 1 or more, 1.5 or more, 2 or more, or 2.5 or more. This may be a technical intention to secure favorable conditions for producing flower-shaped particles by setting the molar ratio of zinc to phosphorus to be equal to or higher than that of zinc when mixing the zinc source material and the phosphorus source material, as can be confirmed through one embodiment of the present invention.

[0016] In the above method, the step of mixing the zinc source solution and the phosphorus source solution may be a step of mixing such that the molar ratio of zinc to phosphorus is 1 to 5, 1 to 4.5, 1 to 4, 1 to 3.5, 1 to 3, 1 to 2.5, 1.5 to 5, 1.5 to 4.5, 1.5 to 4, 1.5 to 3.5, 1.5 to 3, 1.5 to 2.5, 2 to 5, 2 to 4.5, 2 to 4, 2 to 3.5, 2 to 3, or 2 to 2.5; preferably, the molar ratio is 1 to 5, most preferably 1 to 3 or 1.5 to 2.5, in order to appropriately maintain a flower-shaped form beyond a simple plate-like form while not excessively increasing the complexity of the particles themselves to more clearly display the flower shape. It may be a mixing step, but is not limited to this.

[0017] The above method may further include the step of preparing a zinc source solution under acidic conditions by dissolving a compound containing zinc ions, which is based on the discovery that flower-shaped Zn-PO-based zinc phosphate particles are produced more reproducibly under acidic conditions. The above acidic conditions may be 6.5 pH or lower, 6.0 pH or lower, 5.5 pH or lower, 5.0 pH or lower, 4.5 pH or lower, 4.0 pH or lower, 3.5 pH or lower, 3.0 pH or lower, 2.5 pH or lower, 2.0 pH or lower, 1.5 pH or lower, or 1.0 pH or lower. In order to prevent the appearance of an unclear flower shape due to excessively increasing the complexity of the particles themselves when maintaining excessive acidity, and to prevent the problem of not being able to produce consistent flower-shaped particles when maintaining too low acidity, the conditions may preferably be 6.0 pH or lower, and more preferably 4.0 to 6.0 pH, 4.0 to 5.5 pH, or 4.0 to 5.0 pH, but are not limited thereto.

[0018] In the above method, the compound containing the zinc ion may be at least one selected from the group consisting of zinc chloride (ZnCl2), zinc nitrate (Zn(NO3)2), zinc sulfate (ZnSO4), zinc acetate (Zn(CH3COO)2), zinc hydroxide (Zn(OH)2), and zinc oxide (ZnO), and may preferably be zinc chloride (ZnCl2) in order to advantageously achieve the desired acidic conditions of the zinc ion source solution, but is not limited thereto.

[0019] In the above method, the step of preparing the zinc source solution may be a step of preparing a zinc source solution in a transparent and homogeneous state, which may reflect the technical intention that if precipitates are present in the zinc source solution or if it remains opaque and heterogeneous, flower-shaped particles may not be consistently formed.

[0020] The above method may further include the step of dissolving a phosphate compound to prepare a phosphorus source solution under basic conditions, which is based on the discovery that flower-shaped Zn-PO-based zinc phosphate particles are produced more reproducibly under basic conditions. The basic conditions may be 7.5 pH or higher, 8.0 pH or higher, 8.5 pH or higher, 9.0 pH or higher, 9.5 pH or higher, 10.0 pH or higher, 10.5 pH or higher, 11.0 pH or higher, 11.5 pH or higher, 12.0 pH or higher, 12.5 pH or higher, or 13.0 pH or higher. Considering that maintaining a basicity that is too low or too high causes an excessive increase in the randomness of the shape itself during particle formation, the conditions may preferably be 8.0 pH or higher, and more preferably 8.0 to 10.0 pH or 8.5 to 9.5 pH, but are not limited thereto.

[0021] In the above method, the phosphate compound may be at least one selected from the group consisting of phosphoric acid (H3PO4), sodium dihydrogen phosphate (NaH2PO4), sodium hydrogen phosphate (Na2HPO4), sodium phosphate (Na3PO4), ammonium hydrogen phosphate ((NH4)2HPO4), and calcium phosphate (Ca3(PO4)2), and preferably may be sodium hydrogen phosphate (Na2HPO4) in order to advantageously achieve the desired basic conditions of the phosphorus source solution, but is not limited thereto.

[0022] In the above method, the stirring step may be a step of stirring the mixed solution for a time of 120 minutes or less, 100 minutes or less, 80 minutes or less, 60 minutes or less, 40 minutes or less, or 20 minutes or less, and preferably a step of stirring for a time of 60 minutes or less to provide sufficient time for the reaction between zinc ions and phosphorus ions to form particles, while preventing the reaction from exceeding the complexity of the particles themselves or excessively increasing the randomness of the shape, more preferably a step of stirring for a time of 30 minutes or less, or 10 to 30 minutes or less, but is not limited thereto.

[0023] In the above method, the stirring step may further include the step of obtaining a stirred solution under acidic conditions, which is based on the discovery that flower-shaped Zn-PO-based zinc phosphate particles are produced more reproducibly when the final stirred solution maintains acidic conditions. The above acidic conditions may be 6.5 pH or lower, 6.0 pH or lower, 5.5 pH or lower, 5.0 pH or lower, 4.5 pH or lower, 4.0 pH or lower, 3.5 pH or lower, 3.0 pH or lower, 2.5 pH or lower, 2.0 pH or lower, 1.5 pH or lower, or 1.0 pH or lower. In order to prevent the appearance of an unclear flower shape due to excessively increasing the complexity of the particles themselves when maintaining excessive acidity, and to prevent the problem of not being able to produce consistent flower-shaped particles when maintaining too low acidity, the condition may preferably be 6.0 pH or lower, and more preferably may be 1.5 to 3.5 pH, 1.5 to 3.0 pH, or 2.0 to 3.0 pH, but is not limited thereto.

[0024] In the above method, the stirring step may be a stirring step under conditions of 200 to 1000 RPM, 200 to 900 RPM, 200 to 800 RPM, 200 to 700 RPM, 200 to 600 RPM, 200 to 500 RPM, or 200 to 400 RPM, and according to a preferred embodiment, may be a stirring step under conditions of 200 to 400 RPM, but is not limited thereto.

[0026] In one aspect of the present invention, flower-shaped Zn-PO-based zinc phosphate particles are provided, which are manufactured by the above method and have plate-shaped crystals radially clustered toward the center.

[0027] In the above particles, at least 2, 3, 4, 5, 6, 7, 8, 9, or 10 plate-like crystals may be arranged and aggregated radially toward the center.

[0028] In the above particle, a cavity may be formed in the center to penetrate both sides of the plate-shaped crystals, and the cavity may be circular, square, rhombus-shaped, or other irregular shapes, and there are no special restrictions on the shape, and it is sufficient that it is formed to penetrate both sides.

[0029] In the above particles, the plate-shaped crystals may be symmetrically arranged and aggregated toward the center, which may mean that the particles more clearly reveal a flower-shaped form, and it is sufficient that when observing the external appearance of the particles, the plate-shaped crystals are symmetrically arranged and aggregated with respect to the center, and is not limited to the geometric definition of such symmetry.

[0030] In the above particles, the X-ray diffraction (XRD) analysis results may show a peak at at least one selected from diffraction angles (2θ) of 39.4±0.3˚ and 60.7±0.3˚, which may not appear in the X-ray diffraction analysis results of Hopeite.

[0031] In the above particles, the X-ray diffraction analysis results may not show a peak at at least one selected from diffraction angles (2θ) of 17.3±0.3˚, 33.9±0.3˚, 34.6±0.3˚ and 60.0±0.3˚, and this may be the result of X-ray diffraction analysis of hopate.

[0032] In the above particles, the intensity of the peak appearing at at least one selected from the diffraction angles (2θ) of 19.4±0.3˚, 22.0±0.3˚, 25.6±0.3˚, 26.2±0.3˚, 31.2±0.3˚, 34.3±0.3˚, 39.6±0.3˚ and 46.8±0.3˚ in the X-ray diffraction analysis results may be reduced to 80% or less compared to the intensity of the peak appearing in the X-ray diffraction analysis results of hopate.

[0033] In the above particles, the intensity of the peak appearing at at least one selected from the diffraction angles (2θ) of 22.0±0.3˚, 25.6±0.3˚, 26.2±0.3˚, 31.2±0.3˚, 34.3±0.3˚, 39.6±0.3˚ and 46.8±0.3˚ in the X-ray diffraction analysis results may be reduced to 40% or less compared to the intensity of the peak appearing in the X-ray diffraction analysis results of hopate.

[0034] In the above particles, the intensity of the peak appearing at at least one selected from the diffraction angles (2θ) of 22.0±0.3˚, 25.6±0.3˚, 26.2±0.3˚, 34.3±0.3˚, 39.6±0.3˚ and 46.8±0.3˚ in the X-ray diffraction analysis results may be reduced to 30% or less compared to the intensity of the peak appearing in the X-ray diffraction analysis results of hopate.

[0035] In the above particles, the intensity of the peak appearing at at least one selected from the diffraction angles (2θ) of 22.0±0.3˚ and 39.6±0.3˚ in the X-ray diffraction analysis results may be reduced to 20% or less compared to the intensity of the peak appearing in the X-ray diffraction analysis results of hopate.

[0036] In the above particles, the area of ​​the peak appearing at at least one selected from the diffraction angles (2θ) of 9.7±0.3˚, 19.4±0.3˚, 22.0±0.3˚, 25.6±0.3˚, 26.2±0.3˚, 31.2±0.3˚, 34.3±0.3˚, 39.6±0.3˚ and 46.8±0.3˚ in the X-ray diffraction analysis results may be reduced to 10% or less compared to the area of ​​the peak appearing in the X-ray diffraction analysis results of hopate.

[0037] In the above particles, the area of ​​the peak appearing at at least one selected from the diffraction angles (2θ) of 22.0±0.3˚, 25.6±0.3˚, 26.2±0.3˚, 31.2±0.3˚ and 34.3±0.3˚ in the X-ray diffraction analysis results may be reduced to 5% or less compared to the area of ​​the peak appearing in the X-ray diffraction analysis results of hopate.

[0038] In the above particles, the average length in the direction of the major axis of each of the plate-shaped crystals may be 20 to 100 μm, 20 to 90 μm, 20 to 80 μm, 20 to 70 μm, 20 to 60 μm, 25 to 55 μm, or 30 to 50 μm, preferably 20 to 60 μm or 30 to 50 μm, but is not limited thereto.

[0039] In the above particles, the circularity value derived by the following mathematical formula 1 may be 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less, and according to a preferred embodiment, may be 0.3 or less, or 0.1 to 0.2, but is not limited thereto:

[0040] [Mathematical Formula 1]

[0041] Sphericity = 4π x Total particle area / Total particle perimeter 2 .

[0042] In the above particles, the convexity value derived by the following mathematical formula 2 may be 0.5 to 0.9, 0.5 to 0.8, or 0.5 to 0.7, and according to a preferred embodiment, may be 0.5 to 0.7, but is not limited thereto:

[0043] [Mathematical Formula 2]

[0044] Convexity = Convex Hull Circumference / Total Particle Circumference

[0045] In the above particles, the solidity value derived by the following mathematical formula 3 may be 0.4 to 0.8, 0.4 to 0.7, or 0.5 to 0.7, and according to a preferred embodiment may be 0.5 to 0.7, but is not limited thereto:

[0046] [Mathematical Formula 3]

[0047] Thickness = Total particle area / Convex hull area

[0049] As one embodiment of the present invention, a cosmetic composition comprising the above particles is provided.

[0050] In the above cosmetic composition, flower-shaped Zn-PO-based zinc phosphate particles are included in the cosmetic composition and can be used without limitation for any purpose where they can exert an effect, and preferably, they can be used for UV protection. In this case, based on the excellent UV protection properties of the particles, there is a technical excellence in that it can block more than 60% of UV rays in the wavelength range of 200 to 400 nm and more than 80% of UV rays in the wavelength range of 300 to 400 nm, which indicates a performance capable of blocking even the range that materials typically used as UV protection materials cannot block.

[0051] In the above cosmetic composition, in addition to the particles, it may include ingredients commonly used in cosmetic compositions, such as conventional auxiliary agents like antioxidants, stabilizers, solubilizers, vitamins, pigments, and fragrances, and carriers.

[0052] Products to which the above cosmetic composition can be added include, for example, cosmetics such as astringent lotions, softening lotions, nourishing lotions, various creams, essences, packs, foundations, etc., as well as cleansing products, facial cleansers, soaps, treatments, beauty solutions, etc., but are not limited thereto.

[0053] Specific formulations of the above cosmetic composition include skin lotion, skin softener, skin toner, astringent, lotion, milk lotion, moisture lotion, nourishing lotion, ointment, cream, massage cream, nourishing cream, moisture cream, hand cream, essence, nourishing essence, pack, soap, shampoo, cleansing foam, cleansing lotion, cleansing cream, body lotion, body cleanser, emulsion, lipstick, makeup base, foundation, pressed powder, loose powder, eyeshadow, mist, etc. Effects of the invention

[0055] A manufacturing method provided as one embodiment of the present invention relates to a method for manufacturing flower-shaped Zn-PO-based zinc phosphate particles having a unique shape, and is based on establishing an optimal manufacturing protocol to obtain specific physical properties and shapes compared to conventionally known zinc phosphate particles by specifically setting the molar ratio between reactants and reaction conditions. Since the particles manufactured therefrom exhibit differentiated technical effects compared to conventional technology based on their uniqueness, their practical value is expected to be high.

[0056] However, it should be understood that the effects are not limited to those mentioned above and include all effects that can be inferred from the composition of the invention described in the detailed description or claims. Brief explanation of the drawing

[0058] FIG. 1 shows the shape of the generated particles according to the transparency (homogeneity) and pH conditions of the zinc (Zn) source material presented as an embodiment of the present invention. Figure 2 shows the shape of the generated particles according to the molar ratio of zinc (Zn) and phosphorus (P), presented as an embodiment of the present invention. Figures 3 and 4 show the shape of the generated particles according to the stirring (reaction) time between the zinc source material and the phosphorus source material, as presented as an embodiment of the present invention. FIG. 5 shows the shape of the generated particles according to the pH conditions of the phosphorus source material, presented as an embodiment of the present invention. Figure 6 is a photograph of the final manufactured flower-shaped particle powder presented as an embodiment of the present invention. FIGS. 7 and 8 are photographs of flower-shaped particles presented as an embodiment of the present invention, taken at different magnifications and angles, respectively. FIG. 9 is an SEM image and an SEM-EDS image of a flower-shaped particle presented as an embodiment of the present invention. Figure 10 is EDS spectrum data obtained by analyzing flower-shaped particles presented as an embodiment of the present invention using the eZAF Quant method. Figures 11 to 13 compare XRD data between flower-shaped particles (ZnPO4) and hopeite particles presented as an embodiment of the present invention. Figure 14 shows the results of an experiment to confirm the ultraviolet blocking ability of flower-shaped particles (ZnPO4) presented as an embodiment of the present invention. Specific details for implementing the invention

[0059] Hereinafter, to explain more specifically, examples and experimental examples will be described in detail. However, the following examples and experimental examples are illustrative and the scope of the invention is not limited thereto.

[0061] Example 1. Preparation of flower-shaped particles

[0063] As a zinc source material, a compound containing zinc is dissolved in water, and if necessary, heated for a short time at 40 to 60°C and then cooled to room temperature (20 to 30°C). As a phosphorus source material, a compound containing phosphorus is dissolved in water and stirred at room temperature (20 to 30°C) to completely dissolve it.

[0064] Slowly pour the zinc source material along the wall of a beaker containing the phosphorus source material and stir under conditions of room temperature (20 to 30°C) (stirring speed 200 to 400 rpm). A white precipitate is formed immediately, and sufficient stirring is performed to allow the particles to grow and self-assemble.

[0065] After a sufficient amount of time has passed, stirring is stopped and the solids are allowed to settle, after which the supernatant is removed. The mixture is washed 1 to 3 times with distilled water to remove residual ions, and to increase drying efficiency and reduce aggregation, sequential additional washing can be performed 1 to 2 times with 70% ethanol and 95 to 99.5% ethanol.

[0066] Afterwards, the powder is dried at 80°C for about 2 hours to obtain the final flower-shaped particle powder (Fig. 6).

[0068] Example 2. Particle shape according to the state of the zinc source material

[0070] We intended to verify the shape of the final particles produced according to the transparency and pH conditions of the zinc source material. The manufacturing method of Example 1 was carried out as is, but zinc chloride (ZnCl2) was selected as the zinc-containing compound and sodium hydrogen phosphate (Na2HPO4) was selected as the phosphorus-containing compound. The moles of phosphorus (P) were fixed while the moles of zinc (Zn) were varied slightly, and the transparency (homogeneity) and pH conditions of the zinc source material were varied. When fine precipitation occurred and the mixture became opaque, a small amount of inorganic acid (e.g., HCl) was titrated to control the acidity and transparency. The specific conditions and the results of observing the shape of the final particles produced are shown in Table 1 below.

[0071] Zn:P molar ratio ZnCl 2 input ZnCl 2 transparency Zn confiscation P confiscation pH Particle shape 2.5:1 4.60g transparency 0.03375 0.013469 4.5 to 5.0 Flower-like 1.25:1 2.30g opacity 0.01688 0.013469 5.46 Plate-like 0.5:1 0.92g opacity 0.00675 0.013469 5.63 Blocky 0.25:1 0.46g opacity 0.00338 0.013469 5.90 Sparkle-like

[0072] As can be seen in Table 1 and Figure 1 above, when intermediate phases or precipitates are formed in the zinc source material, resulting in an opaque form, consistent flower-shaped particles are not formed, and particles that are simply aggregated or have increased irregularity are produced. On the other hand, when the zinc source material maintains a transparent and homogeneous solution state without intermediate phases or precipitates, it was confirmed that consistent and relatively standardized flower-shaped particles are formed.

[0073] This shows that, when manufacturing flower-shaped particles, maintaining the zinc source material in a transparent and homogeneous state is an important condition for preventing the appearance of such shapes.

[0075] Example 3. Particle shape according to the molar ratio of zinc and phosphorus.

[0077] As confirmed in Example 2 above, the zinc source material was fixed in a transparent and homogeneous state, and the optimal conditions for generating flower-shaped particles were explored by adjusting the molar ratio of zinc (Zn) and phosphorus (P). The preparation method of Example 1 was retained, but zinc chloride (ZnCl2) was selected as the zinc-containing compound and sodium hydrogen phosphate (Na2HPO4) as the phosphorus-containing compound, respectively; the moles of phosphorus (P) were fixed, while the moles of zinc (Zn) were varied slightly. The specific conditions and the results of observing the final particle shapes are shown in Table 2 below (zinc source material: 0.23 g / mL; transparent and homogeneous solution).

[0078] Zn:P molar ratio Amount of zinc source material input Phosphorus source material input amount Zinc source material pH pH after stirring Particle shape 5.0:1 43.9mL 25mL 4.5-5.0 1.77 flower shape 2.5:1 21.95mL 25mL 4.5-5.0 2.24 flower shape 2.0:1 17.56mL 25mL 4.5-5.0 2.33 flower shape 1.0:1 8.78mL 25mL 4.5-5.0 2.74 flower shape 0.5:1 4.9mL 25mL 4.5-5.0 4.97 mix

[0079] As can be seen in Table 2 and Figure 2 above, when zinc was mixed at a low molar ratio relative to phosphorus, it failed to produce a flower shape and instead generated sparkle-like, cube-like, or randomly irregular shapes that could not be defined by a specific form. However, when zinc was mixed at an equal or higher molar ratio relative to phosphorus, the randomly irregular shapes significantly disappeared, and it was observed that numerous flower-shaped particles were generated. In particular, starting from cases where the molar ratio of zinc to phosphorus was 2 or higher, plate-like particles that failed to form a flower shape disappeared, and only distinct flower-shaped particles were formed. Furthermore, as the molar ratio of zinc to phosphorus increased, the complexity of the flower-shaped particles improved, and the number of plate-like crystals arranged radially and aggregated toward the center increased. When the molar ratio of zinc to phosphorus was 5 or higher, the complexity increased excessively, and the degree of aggregation toward the center became excessively high, resulting in the generation of particles that were difficult to visually identify as flower-shaped.

[0080] Considering all these points, it can be confirmed that setting the molar ratio of zinc to phosphorus to be 1 or greater is a favorable condition for producing flower-shaped particles, and most preferably, setting it to be 2 or greater is a favorable condition. Furthermore, it can be concluded that setting it to 2 is preferable in terms of considering manufacturing production costs when applying on a mass scale.

[0082] Example 4. Particle shape according to phosphorus source material and stirring time

[0084] We aimed to explore the optimal conditions for generating flower-shaped particles by examining how the particle shape changes when the phosphorus source material and stirring time are varied. While maintaining the manufacturing method conditions of Example 1, we adopted the optimized conditions from Examples 2 and 3. The zinc source material was set to a solution containing zinc chloride (ZnCl2) at a pH of 4.5–5.0, and the molar ratio of zinc to phosphorus was set to 2:1. Phosphoric acid (H3PO4), sodium dihydrogen phosphate (NaH2PO4), sodium hydrogen phosphate (Na2HPO4), and sodium phosphate (Na3PO4) were used as the phosphorus source materials, respectively, and the stirring time was also varied. When sodium dihydrogen phosphate (NaH2PO4) was used as the phosphorus-containing compound, the stirring time was fixed at 20 minutes, but the pH of the phosphorus source material was adjusted by titration with sodium hydroxide (NaOH), and we intended to verify the changes in particle shape resulting from these variations. The results of observing the specific conditions and the final particle shape are as shown in Table 3 below.

[0085] Phosphorus source material pH hour Particle shape Na2HPO4 9.0-9.2 20 minutes flower shape Na2HPO4 9.0-9.2 2 hours Flower shape, plate-like mixture Na2HPO4 9.0-9.2 24 hours Flower shape, plate-like mixture Na2HPO4 9.0-9.2 48 hours Flower shape, plate-like mixture H3PO4 2.0 20 minutes Not formed Na3PO4 10.5 20 minutes Arbitrary, irregular Na3PO4 10.5 24 hours Arbitrary, irregular Na3PO4 10.5 48 hours Arbitrary, irregular NaH2PO4 4.5 20 minutes thin hexagonal piece NaH2PO4 5.0 20 minutes Arbitrary, irregular NaH2PO4 7.0 20 minutes Arbitrary, irregular NaH2PO4 8.0 20 minutes Arbitrary, irregular NaH2PO4 9.0 20 minutes Arbitrary, irregular NaH2PO4 11.0 20 minutes Arbitrary, irregular

[0086] As can be seen from Table 3, Figures 3 and 4 above, when sodium hydrogen phosphate (Na2HPO4) was used as the phosphorus source material, as the stirring time increased, the number of particles maintaining a flower shape decreased and the number of plate-shaped particles increased. In particular, it was observed that the proportion of plate-shaped particles was significantly higher compared to flower-shaped particles when stirred for 24 and 48 hours, and when stirred for 48 hours, the proportion of plate-shaped particles was so high that it was difficult to find flower-shaped particles. This demonstrates that the formation of flower-shaped particles is highly sensitive to the setting of the stirring time between the zinc source compound and the phosphorus source compound.

[0087] In addition, when sodium phosphate (Na3PO4) was used as the phosphorus source material, very coarse flower-shaped particles were produced, but overall, the shape of the particles was random and amorphous regardless of the stirring time.

[0088] In addition, when phosphoric acid (H3PO4) was used as the phosphorus source material, no particles were formed, and when sodium dihydrogen phosphate (NaH2PO4) was used as the phosphorus source material, the shape of the particles was random and amorphous regardless of pH conditions (Fig. 5).

[0089] Considering these points comprehensively, it can be confirmed that the shape of the particles ultimately produced varies significantly depending on which phosphoric acid source material is used and how the stirring time is set; thus, it can be confirmed that the manufacturing method presented as an embodiment of the present invention is sensitively controlled by the steps and conditions constituting it.

[0091] Example 5. Analysis of flower-shaped particles

[0093] 1. SEM Analysis

[0095] As can be seen in FIGS. 7 and 8, the flower-shaped particles produced through the embodiment of the present invention have at least four (mainly four) plate-shaped crystals (or petals) arranged radially toward the center and aggregated, and a hole is formed in the center, which is formed to penetrate both sides of the plate-shaped crystals. In particular, it can be confirmed that the plate-shaped crystals in the flower-shaped particles produced through the embodiment of the present invention have a very symmetrical and very regular shape. To analyze more specific morphological characteristics, the surface area, perimeter, anisotropy, sphericality, convexity, and solidity were measured, as shown in Table 4 below.

[0096] Measurement items Measured value Calculation method analysis Surface size 57098.5μm 2 Total area of ​​the particle (2D projected area) - Four petal-like crystals aggregate at the center to form a flower shape - Major axis of Crystal A: 40.71 μm, Major axis of Crystal B: 44.80 μm, Major axis of Crystal C: 40.37 μm, Major axis of Crystal D: 39.61 μm outer perimeter 2226.5μm outer perimeter complex and long outlines Anisotropy 0.95~1.0 Ratio of the major axis to the minor axis Four-directional symmetry, small difference in length between petals Spherical shape 0.1447 4π x Total particle area / Total particle perimeter 2 Very low, complex petal-shaped structure Convexity 0.6982 Convex Hull Circumference / Total Particle Circumference Not convex Durability 0.6123 Total particle area / Convex hull area The interior is hollowed out, with spaces existing between the plate-shaped crystals (petals).

[0097] The characteristics of the flower-shaped particles produced through the embodiments of the present invention shown in Table 4 above are radial aggregate shape characteristics not observed in typical hopeite, showing that each petal aggregates at the center to form a multi-directional (mainly four-directional) flower-shaped arrangement. This is presumed to exhibit mixed-phase or structurally distorted polycrystalline characteristics that distinguish it from typical hopeite and single crystals.

[0098] In addition, to determine the atomic composition of the flower-shaped particles produced through the embodiments of the present invention, atomic ratios were verified using SEM-EDS analysis and the eZAF Quant method. The results of the eZAF Quant analysis are shown in Table 5 below.

[0099] element weight% Minimum Detect Limit (MDL) atom% OK 47.3 0.56 74.0 PK 13.6 0.57 11.0 Zn K 39.1 2.63 15.0 Pt L 0.0 0.00 0.0

[0100] When combining the SEM-EDS analysis results and eZAF Quant analysis results of Table 5, Fig. 9, and Fig. 10, it can be confirmed that the flower-shaped particles produced through the embodiment of the present invention contain zinc (Zn), phosphorus (P), and oxygen (O) as major constituent elements. In particular, judging from the high atomic ratio of oxygen (O), it is determined that the particles have a zinc phosphate-based structure of the Zn-PO ternary system.

[0102] 2. XRD Data Analysis

[0104] In order to more specifically identify the distinctiveness of the flower-shaped particles produced through the embodiments of the present invention, XRD pattern data was analyzed, and the characteristics were to be clarified by comparing them with the XRD pattern data of typical and well-known hopeite. The XRD pattern of the flower-shaped particles produced through the embodiments of the present invention was deconvolved using Gaussian peak fitting based on approximately 20 or more peaks, and each peak was modeled as a Gaussian with an individual center, amplitude, width, and area. In addition, whether each peak matched typical hopeite was analyzed individually (Figs. 11 to 13). The analysis results are shown in Table 6 below, and it can be confirmed that unique peaks not found in hopeite appear at the 9th and 14th peaks.

[0105] peak Center(2θ, ˚) century(%) Width(FWHM est., ˚) Area (au) Matching status with Hopate 1 9.763 95.58 0.0356 8.53 O 2 19.493 78.02 0.044 8.6 O 3 20.199 6.54 0.0621 1.02 O 4 22.281 6.11 0.0597 0.92 O 5 25.783 10.91 0.0593 1.62 O 6 26.353 10.11 0.0608 1.54 O 7 31.41 31.19 0.0639 5.0 O 8 34.363 7.57 0.0742 1.41 O 9 39.442 7.99 0.0634 1.27 X 10 39.771 4.53 0.1368 1.55 O 11 43.127 5.23 0.0912 1.19 O 12 45.366 4.84 0.0971 1.18 O 13 46.896 10.64 0.0939 2.5 O 14 60.737 8.28 0.1388 2.88 X

[0106] Additionally, we intended to determine whether there were any peaks among the major peaks appearing in the XRD pattern of hopate that did not appear in the XRD pattern of the flower-shaped particles prepared through the embodiment of the present invention, and if there were any matching peaks, to what extent they differed in terms of intensity and area. The results of this comparative analysis are shown in Table 7 below.

[0107] peak Center(2θ,˚) Hopate peak intensity (A,%) Flower-shaped particle peak intensity (B,%) B / A ratio (%) Hopate peak area Ratio of flower-shaped particle peak area to hopate peak area (%) 1 9.776 100.0 95.58 0.956 8.53 0.085 2 17.388 30.0 0.0 0.0 0.0 0.0 3 19.407 100.0 78.02 0.78 8.6 0.086 4 22.094 40.0 6.11 0.153 0.92 0.023 5 25.696 50.0 10.91 0.218 1.62 0.032 6 26.299 50.0 10.11 0.202 1.54 0.031 7 31.282 100.0 31.19 0.312 5.0 0.05 8 33.928 30.0 0.0 0.0 0.0 0.0 9 34.33 30.0 7.57 0.252 1.41 0.047 10 34.631 30.0 0.0 0.0 0.0 0.0 11 39.654 30.0 4.53 0.151 1.55 0.052 12 46.865 40.0 10.64 0.266 2.5 0.063 13 60.024 40.0 0.0 0.0 0.0 0.0

[0108] As can be seen in Table 7 above, the peaks near diffraction angles (2θ) 17.388˚, 33.928˚, 34.631˚, and 60.024˚ present in the hopate XRD pattern have disappeared in the XRD pattern of the flower-shaped particles prepared through the embodiment of the present invention. In addition, it can be confirmed that the intensity of the peaks near diffraction angles (2θ) 19.407˚, 22.094˚, 25.696˚, 26.299˚, 31.282˚, 34.33˚, 39.654˚, and 46.865˚ present in the hopate XRD pattern has decreased to 80% or less compared to the intensity of the peaks appearing in the hopate XRD pattern.

[0109] Furthermore, among these, the intensity of the peaks near 22.094˚, 25.696˚, 26.299˚, 31.282˚, 34.33˚, 39.654˚, and 46.865˚ was reduced to less than 40%, the intensity of the peaks near 22.094˚, 25.696˚, 26.299˚, 34.33˚, 39.654˚, and 46.865˚ was reduced to less than 30% compared to the intensity of the peaks appearing in the XRD pattern of hopate, and the intensity of the peaks near 22.094˚ and 39.654˚ was reduced to less than 20% compared to the intensity of the peaks appearing in the XRD pattern of hopate.

[0110] Analysis in terms of area showed a greater difference than analysis in terms of intensity, with the areas of peaks near 9.776˚, 19.407˚, 22.094˚, 25.696˚, 26.299˚, 31.282˚, 34.33˚, 39.654˚, and 46.865˚ reduced to less than 10% of the peak areas appearing in the XRD pattern of hopate.

[0111] Furthermore, among these, the area of ​​the peaks near 22.094˚, 25.696˚, 26.299˚, 31.282˚, and 34.33˚ was reduced to less than 5% of the peak area appearing in the XRD pattern of hopate.

[0112] When considering these points comprehensively, it is predicted that the flower-shaped particles produced through the embodiments of the present invention may have undergone partial crystal distortion or phase separation in the hopate structure, and it can be seen that scientific grounds have been confirmed to view them as independent phases or modified phases having distinct structural differences due to differences in crystallinity or composition relative to the hopate structure.

[0114] Example 6. UV blocking effect of flower-shaped particles

[0116] The UV blocking ability of the flower-shaped particle powder prepared through the embodiment of the present invention was analyzed using a spectrophotometer (hereinafter "UV / VIS-NIR equipment") capable of measuring the ultraviolet-visible-near-infrared region. The equipment is equipped with a DRA (Diffuse Reflectance Accessory, integrating sphere) module for measuring diffuse reflection and is configured to measure reflectance as an R(%) value. The diffuse reflection spectrum of the sample was obtained by performing a continuous scan of the flower-shaped particle powder prepared through the embodiment of the present invention over the ultraviolet and visible light wavelength range from 175 nm to 800 nm. The measurement was repeated under the same conditions, and the average of the repeated measurements was used as the final reflectance value.

[0117] As can be seen in Fig. 14, it can be confirmed that the flower-shaped particles manufactured through the embodiment of the present invention exhibit excellent UV blocking ability in the entire UV range, and in particular, it was confirmed that they block UV rays in the wavelength range of 300 to 400 nm, which is known to reach the surface the most, at a significantly superior rate compared to TiO2 and ZnO, which are known as conventional UV blocking materials.

[0118] In summary, it can be interpreted that the flower-shaped particles produced through the embodiments of the present invention can be excellently utilized as sunscreens by being included in cosmetic compositions, etc.

[0120] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A method for producing flower-shaped Zn-PO-based zinc phosphate particles, comprising the steps of: mixing a zinc source solution and a phosphorus source solution such that the molar ratio of zinc to phosphorus is 2 or more; and stirring the mixed solution. Claim 2 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, wherein the mixing step is a step of mixing a zinc source solution and a phosphorus source solution such that the molar ratio of zinc to phosphorus is 2 to 5. Claim 3 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, further comprising the step of dissolving a compound containing zinc ions to prepare a zinc source solution under acidic conditions. Claim 4 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 3, wherein the acidic conditions are conditions of pH 6.0 or lower. Claim 5 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 3, wherein the compound containing the zinc ion is at least one selected from the group consisting of zinc chloride (ZnCl2), zinc nitrate (Zn(NO3)2), zinc sulfate (ZnSO4), zinc acetate (Zn(CH3COO)2), zinc hydroxide (Zn(OH)2) and zinc oxide (ZnO). Claim 6 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 3, wherein the step of producing the zinc source solution is the step of producing a zinc source solution in a transparent and homogeneous state. Claim 7 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, further comprising the step of dissolving a phosphate compound to produce a phosphorus source solution under basic conditions. Claim 8 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 7, wherein the basic condition is a condition of pH 8.0 or higher. Claim 9 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 7, wherein the phosphate compound is at least one selected from the group consisting of phosphoric acid (H3PO4), sodium dihydrogen phosphate (NaH2PO4), sodium hydrogen phosphate (Na2HPO4), sodium phosphate (Na3PO4), ammonium hydrogen phosphate ((NH4)2HPO4), and calcium phosphate (Ca3(PO4)2). Claim 10 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, wherein the stirring step is a step of stirring the mixed solution for a time of 120 minutes or less. Claim 11 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, wherein the stirring step further comprises the step of obtaining a stirred solution under acidic conditions. Claim 12 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 11, wherein the acidic conditions are conditions of pH 6.0 or lower. Claim 13 A method for producing flower-shaped Zn-PO-based zinc phosphate particles according to claim 1, wherein the stirring step is a stirring step under conditions of 200 to 600 RPM. Claim 14 Flower-shaped Zn-PO-based zinc phosphate particles, manufactured by the method of any one of claims 1 to 13, in which plate-like crystals are radially aggregated toward the center. Claim 15 Zn-PO-based zinc phosphate particles according to claim 14, wherein the particles are formed by at least four plate-shaped crystals arranged and aggregated radially toward a center, and a cavity formed in the center to penetrate both sides of the plate-shaped crystals.